Genomic Characterization of Cholangiocarcinoma in Primary Sclerosing Cholangitis Reveals Therapeutic Opportunities. Issue 4 (19th August 2020) - Goeppert, Benjamin; Folseraas, Trine; Roessler, Stephanie; Kloor, Matthias; Volckmar, Anna‐Lena; Endris, Volker; Buchhalter, Ivo; Stenzinger, Albrecht; Grzyb, Krzysztof; Grimsrud, Marit M.; Gornicka, Barbara; von Seth, Erik; et al.
Abstract : Background and Aims: Lifetime risk of biliary tract cancer (BTC) in primary sclerosing cholangitis (PSC) may exceed 20%, and BTC is currently the leading cause of death in patients with PSC. To open new avenues for management, we aimed to delineate clinically relevant genomic and pathological features of a large panel of PSC‐associated BTC (PSC‐BTC). Approach and Results: We analyzed formalin‐fixed, paraffin‐embedded tumor tissue from 186 patients with PSC‐BTC from 11 centers in eight countries with all anatomical locations included. We performed tumor DNA sequencing at 42 clinically relevant genetic loci to detect mutations, translocations, and copy number variations, along with histomorphological and immunohistochemical characterization. Regardless of the anatomical localization, PSC‐BTC exhibited a uniform molecular and histological characteristic similar to extrahepatic cholangiocarcinoma. We detected a high frequency of genomic alterations typical of extrahepatic cholangiocarcinoma, such as TP53 (35.5%), KRAS (28.0%), CDKN2A (14.5%), and SMAD4 (11.3%), as well as potentially druggable mutations (e.g., HER2 / ERBB2 ). We found a high frequency of nontypical/nonductal histomorphological subtypes (55.2%) and of the usually rare BTC precursor lesion, intraductal papillary neoplasia (18.3%). Conclusions: Genomic alterations in PSC‐BTC include a significant number of putative actionable therapeutic targets. Notably, PSC‐BTC shows a distinct extrahepatic morpho‐molecular phenotype, independent of the anatomical location of the tumor. These findings advance our understanding of PSC‐associated cholangiocarcinogenesis and provide strong incentives for clinical trials to test genome‐based personalized treatment strategies in PSC‐BTC.